1970
DOI: 10.1002/lipi.19700721104
|View full text |Cite
|
Sign up to set email alerts
|

Über die Herstellung von α‐Sulfofettsäureestern

Abstract: Es wurde ein Verfahren zur kontinuierlichen u-Sulfonierung \on Estern gesattigter Fettsauren mit SO, ausgearbeitet und ein spezielles Bleichverfahren fur diese Produkte entwickelt. Der Umsatz, also der Sulfoniergrad, liegt bei 95-99 o/o. Losungsmittel, weitere Verarbeitungsstufen oder Reinigungsoperationen zur Abtrennung von Nebenprodukten sind nicht erforderlich. Preparation of Esters of a-Sulfo-Fatty AcidsA process for the continuous a-sulfonation of saturated fatty acid esters with SO, was worked out and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Contribution to the technical sulfonation of saturated fatty acid esters with air-SO3 given at Henkel & Cie GmbH have been reported (31,32). The reaction of SO3 with fatty esters, such as methyl esters, proceeds in two steps.…”
Section: Fatty Acids and Estersmentioning
confidence: 99%
“…Contribution to the technical sulfonation of saturated fatty acid esters with air-SO3 given at Henkel & Cie GmbH have been reported (31,32). The reaction of SO3 with fatty esters, such as methyl esters, proceeds in two steps.…”
Section: Fatty Acids and Estersmentioning
confidence: 99%
“…A slightly different form of the above mechanism for the 0~-sulfonation of the higher fatty esters is discussed in a paper by Stein et al (9,10). They also propose two stages in their mechanism; the first stage being the addition of SO 3 to the carbonyl oxygen of the ester, which is a rapid 549 (SD&C 77)…”
Section: A-sulfo Fatty Estermentioning
confidence: 99%
“…Stein et al (9,10) have graphically depicted the hydrolytic stability of palm-kernel and coco methyl ester sulfonate by plotting % hydrolysis/hr as a function of temperature and pH at a concentration of 3.4 g of ester sulfonatefliter in aqueous solution, i.e., a concentration which corresponds to concentration in washing solution. They found that at temperatures of up to 60 C the ester hydrolysis was very slow between pH 3-9.5.…”
Section: Hydrolytic Stabilitymentioning
confidence: 99%
See 2 more Smart Citations